The obligatoriness of the vaccination in the brazilian legal system: Compulsory and organization, a comparative analysis of the normative development of the current regulatory framework - Dias, Fernando Ramos Bernardes; Borges, Alexandre Walmott; Assis, Nery dos Santos de (Seven Editora, 2023)
The present article explores analytically the Brazilian legal system about the obligatoriness of the vaccines. The aim of this article is to present the positive evolution of the system of rules on the mandatory vaccine in the Brazilian legal system. The problematization involves questioning how this evolutionary situation occurred and how the rules have been enacted in the national legal system. The inductive methodology of the work was carried out by individualized collection of positive normative documents until the construction of a general framework of all the evolution of norms on mandatory vaccination. The postulate developed on the text seeks to analyze the nature and features of the vaccine compulsoriness, since the questioning about if there is this obligatoriness until the nature of it (administrative nature or criminal nature). The sources used on the essay of the text were bibliographic and documentary sources (various legal texts, such as constitutional, legislative and administrative). The results and conclusion are presented in a synthesis of analysis on the nature and feature of the mandatory vaccination in Brazilian legal system. DOI:https://doi.org/10.56238/interdiinovationscrese-015